Utilização de experimentos de baixo custo e de simulações computacionais no ensino de física em escolas públicas - Nascimento, Adriano Mamedes Silva (2014)
This dissertation work, of the Program Postgraduate in Teaching of Natural Sciences (PPGECN) held by the Federal University of Mato Grosso (UFMT), uses experimental apparatus with low cost materials and computer simulations to aid in the understanding of physics concepts by the student. This methodology was applied at Federal Institute of Education, Science and Technology of Rondônia - IFRO / Campus Ji-paraná, with students of the technical course of Informatics and Chemistry and in a training course for Natural Sciences teachers of EEEFM Aluizio Ferreira, Ji-Paraná/RO and presentation mechanisms for handling software and prototypes for teachers of Physics IFRO. This work aimed to reconcile educational practice with the development of prototypes and their software simulators in PhET (Physics Education Technology). The execution of the activity in the classroom was given by dividing the class into groups. Each group made a register of the assembly process of the prototypes in a report commenting on their experiences of working in groups and the new concepts encountered exploring the experiment and the simulator. All the prepared experiments, tutorials simulators, prototypes and their respective simulations were presented, proposing an implementation plan at a short course made with teachers. This proposal brings benefits to teachers that can use simulations in physics classes. The utilization of experimental and computational resources aid the teacher to explain concepts that otherwise could be difficult for students to understand.